2014
DOI: 10.1002/jobm.201400202
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal properties of an actinomycin D‐producing strain, Streptomyces sp. IA1, isolated from a Saharan soil

Abstract: An actinomycete strain named IA1, which produced an antimicrobial compound, was isolated from a Saharan soil in In Amenas, Algeria. The study of the 16S rDNA sequence of this strain permitted to relate it to Streptomyces mutabilis NBRC 12800(T) (99.93% of similarity). Strain IA1 exhibited strong activity against a wide range of plant pathogenic fungi. One bioactive compound produced in large amounts (46.7 mg L(-1)  day(-1) ), named YA, was isolated and purified by TLC and reverse phase HPLC. The structure eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…2C) or, actinomycin D, actinomycin X2 and actinomycin X 0β (Fig. 4C), found in the inhibition zones produced by the Streptomyces strains 26, 60 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…2C) or, actinomycin D, actinomycin X2 and actinomycin X 0β (Fig. 4C), found in the inhibition zones produced by the Streptomyces strains 26, 60 .…”
Section: Discussionmentioning
confidence: 86%
“…Elaiophylin macrolide and its analogues are well known antibiotics produced by several Streptomyces strains, these macrolides are classified as entities of biological interest 55 presenting a wide range of antibacterial, antifungal, antiinflamatory, enzyme inhibition and anticancer activities 43, 46, 48, 56–59 . The actinomycins present a wide range of antifungal 34, 6064 antibacterial 65 and anticancer 66, 67 properties. On the other hand, the shearinines are alkaloids previously reported from fungi in the genus Eupenicillium and Penicillium .…”
Section: Discussionmentioning
confidence: 99%
“…Compound 47 emerged as the most active in the series, mainly on Gram-positive bacteria and fungi (MICs in the range 1-50 µg/mL corresponding to 4.6-230 µM). [24,81] Valerylpyrrothine (6), Isovalerylpyrrothine (7), Formylpyrrothine (8), Aureothricin (9) antibacterial and antifungal Saccharothrix algeriensis NRRL B-24137, fully sequenced strain Saharan soil [82] Crotonyl-pyrrothine (10), Sorbyl-pyrrothine (11), 2-Hexenyl-pyrrothine (12), 2-Methyl-3-pentenyl-pyrrothine (13) antibacterial and antifungal Saccharothrix algeriensis NRRL B-24137 Saharan soil [83] Benzoyl-pyrrothine dithiolopyrrolone (14) antibacterial, antifungal Saccharothrix algeriensis NRRL B-24137 palm grove soil (Southern Algeria) [84] Mutactimycin PR (15) Toumatia et al [110] and, recently, Djinni et al [111] isolated novel strains producing actinomycin D (49) and showed that genus Streptomyces isolated from Saharan soil of Ain amenas (Streptomyces sp. IA1) and Beni Abbes-Bechar (Streptomyces sp.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…It was first identified from Actinomyces antibioticus in 1940s, later produced by various Streptomyces and Micromonospora species in the world, and also isolated from the Algerian desert soil (Ain Amenas and Beni Abbes)-derived Streptomyces strains Streptomyces sp. IA1 [110,111], demonstrating the effectiveness of the compound for biocontrol against chocolate spots of field bean and Fusarium wilt of flax diseases.…”
Section: Tumor Cells Growth Inhibitorsmentioning
confidence: 99%
“…The cross-streak method (Toumatia et al, 2014) was used to evaluate the antagonistic activities of strain PTL2 against 5 soil-borne phytopathogenic fungi (collection of the LBSM, ENS de Kouba, Alger, Algeria) as test microorganisms: R. solani (LAG3), Fusarium solani (LF22), F. oxysporum f. sp. radicis-lycopersici (LF30), and F. oxysporum f. sp.…”
Section: Antifungal Activitymentioning
confidence: 99%